Correlation of intraoperative frozen section report and histopathological diagnosis: a two-year retrospective study - Kikaniya, Nikita K.; Gupta, Ishankkumar P. (International Journal of Research in Medical Sciences, 2025)
Background: Frozen section is an intraoperative pathological technique which has very important role to play in diagnostics and also it plays important role in further surgical management as specially in oncology setup. The present study was undertaken to assess the degree of diagnostic accuracy of frozen section examination of various anatomical sites, overall accuracy, sensitivity and specificity of frozen section technique. Methods: During the study period from 1st May 2021 to 30th April 2023, a total of 70 patients underwent surgery with intraoperative pathologic consultation for various malignant and non-malignant conditions were reviewed. For frozen section, fresh tissue was sent from the operation theatre to Pathology department and the gross specimens were inspected, dissected and blocks were cut on the cryostat (Leica CM 1950) using Optimal cooling temperature (OCT) compound as embedding medium followed by rapid Haematoxylin-Eosin staining. Results: The most common indications for frozen section encountered in our institute were Sentinel/Locoregional lymph node (57%). Highest number cases were from lymph node (40) followed by thyroid (12), breast tissue (6) etc. Overall diagnostic accuracy of frozen section was 95.7% (67/70 cases). Concordance rate was 95.7% (67 cases), sensitivity 93.9% and specificity 97.2% with positive predictive value 96.7% and negative predictive value 94.7%. Conclusions: Frozen section is the mainstay of rapid diagnosis in histopathology. It is an accurate and reliable method when it is used for suspicious malignancies, tumor resection margin, metastasis of lymph nodes and identification of tissue. It is chiefly performed to determine whether tissue being sampled is malignant or benign.